Appropriate Grammatical Concepts for First-grade Intermediate Students in Kingdom of Saudi Arabia - Alkahtani, Adel Abdullah; Al-Harisi, Jaliyah Hassan Ziydan (Journal of Educational and Psychological Sciences, 2021)
This current research aimed at enumerate and define the grammatical concepts necessary for female students of the first intermediate grade in the intermediate stage, and the research adopted the descriptive survey approach, and the research community consisted of faculty members specialized in Arabic language curricula and its teaching in Saudi universities, and the researchers chose a sample representative of the community in a random way that reached They numbered (13) academically from all Saudi universities, and the researchers prepared a list that included the appropriate grammatical concepts for female students of the first intermediate grade, and the research reached determining the grammatical concepts necessary for female students of the first intermediate grade, and in light of this the researchers recommend an inventory of the grammatical concepts and objectives formulated for each concept, from the current study And other studies related to the link, the formation and control of these concepts, and the training of teachers on them, and enlightening them of the best ways to achieve the goals of each concept. And the necessity of building grammatical concepts hierarchically, so that the relevance of the sub-concepts to the main concept becomes clear, and the necessity of training Arabic language teachers to employ modern strategies to develop grammatical concepts among learners.
Keywords: concepts; grammatical concepts